FACTORS AFFECTING EDUCATIONAL STANDARDS: COSTS, SCHOOL ENVIRONMENT, AND CURRICULUM: (Literature Review MSDM) - Fitri, Yuni; Ali, Hapzi; Rosadi, Kemas Imron (Teunuleh Publisher, 2022)
Past research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and influence of relationships or influences between variables. This article reviews the Factors influencing Educational Standards , namely: Costs , school environment and Curriculum , a literature study of Human Resource Management. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this literature review article are: 1) Costs affect educational standards; 2) the school environment affects the Educational Standards; and 3) The curriculum affects the Education Standards.